The Perfect Match: Assessment of Sample Collection Efficiency for Immunological and Molecular Findings in Different Types of Fabrics. - Zapico, Sara C.; Dytso, Alex; Rubio-Lamia, Leticia Olga; Roca, Gabriela (MDPI, 2022)
Body fluid identification at crime scenes can be crucial in retrieving the appropriate evidence that leads to the perpetrator and, in some cases, the victim. For this purpose, immunochromatographic tests are simple, fast and suitable for crime scenes. The potential sample is retrieved with a swab, normally a cotton swab, moistened in a specific buffer. Nonetheless, there are other swab types available, which have been proven to be efficient for DNA isolation and analysis. The aim of this study is to evaluate the efficiency of different swab types for body fluid identification as well as DNA isolation and characterization. Fifty microliters of human saliva were deposited in three different types of fabric (denim, cotton, and polyester). After 24 h at room temperature, samples were recovered by applying three different swab types, and the tests were performed. Subsequently, total DNA was recovered from the sample buffer. Cotton swabs performed worse in denim and cotton fabrics in both immunochromatography tests and DNA yield. No differences were observed for polyester. In contrast, and except for two replicates, it was possible to obtain a full DNA profile per fabric and swab type, and to identify the mtDNA haplogroup. In this paper, the impact of swab types on body fluid identification through the application of immunochromatographic tests is analyzed for the first time. This work corroborates previous research related to the influence of swab types in nuclear DNA isolation and characterization
Keywords: Fluidos corporales - Análisis; Saliva; Immunochromatographic tests; Cotton swabs; Nylon flocked swabs; STR profile; mtDNA